2018
DOI: 10.1007/978-3-319-95174-4_44
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Gas on Graphene: Pairwise Interaction Potentials

Abstract: Abstract.We investigate different types of potential parameters for the graphene-nitrogen interaction. Interaction energies calculated at DFT level are fitted with the semi-emperical Improved Lennard-Jones potential. Both a pseudo-atom potential and a full atomistic potential are considered. Furthermore, we consider the influence of the electrostatic part on the parameters using different charge schemes found in the literature as well as optimizing the charges ourselves. We have obtained parameters for both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Previous research has shown that coronene and circumcoronene are suitable models to represent graphene at CCSD(T) and B97D levels of theory, respectively. [31][32][33][34] Circumcoronene can be seen as a benzene ring with two concentric rings of benzenes whereby the outermost ring is terminated by dangling hydrogen atoms to avoid wrong electronic structures.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that coronene and circumcoronene are suitable models to represent graphene at CCSD(T) and B97D levels of theory, respectively. [31][32][33][34] Circumcoronene can be seen as a benzene ring with two concentric rings of benzenes whereby the outermost ring is terminated by dangling hydrogen atoms to avoid wrong electronic structures.…”
Section: Computational Detailsmentioning
confidence: 99%
“…From a practical point of view, it seems to be a very robust functional and, among semi-empirical GGA functionals, it is suggested as an efficient and precise method for the study of large systems interacting through dispersion forces. 28 Although the B97D functional has proven its value for non-covalent interactions, [28][29][30][31] this does not guarantee accurate results in a systematic manner for all systems. To overcome this issue, we benchmarked important geometries against CCSD(T) calculations that provide the most trustable physical description of non-covalent interactions in computational chemistry and can therefore be used as reference calculations.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we used intermolecular potentials based on the ILJ potential (Pirani et al, 2004, 2008) to describe the interactions between different gas molecules on one hand and the interactions between the gas molecules and the graphene sheet on the other (Vekeman et al, 2018a,b). Furthermore, we implemented intramolecular interaction potentials in DL_POLY v2.2.…”
Section: Force Fieldsmentioning
confidence: 99%
“…The parameters that were used for the graphene-gas and the gas-gas interactions have been obtained by fitting the ILJ potential, supplemented with a Coulombic sum, to high-level interaction energies at DFT level of the respective systems. The obtained potentials were then benchmarked against DFT and CCSD(T) results as was explained in previous publications (Vekeman et al, 2018a,b). From the results in these articles, here, for both methane and nitrogen, a united-atom and an atomistic model were selected with corresponding partial charges and used for simulations; the used parameters can be found in Table 1.…”
Section: Force Fieldsmentioning
confidence: 99%
See 1 more Smart Citation